Legal Review And Judge's Considerations Regarding The Existence Of Substitute Heirs (Religious Court Decision Number 138/Pdt.P/2021/PA.Grt and Number 68/Pdt.P/2023/PA.JS) - Andi Bintang Oktavinda; Nynda Fatmawati (Universitas Merdeka Madiun, 2026)
Abstract Introduction to the Problem: The main problem in this study is how the similarities and differences in the position of substitute heirs in obtaining their inheritance rights based on Religious Court Decisions Number 138/Pdt.P/2021/PA.Grt and Number 68/Pdt.P/2023/PA.JS, and how the judges view the two decisions. Purpose/Study Objectives: This study aims to analyze the similarities and differences in the application of the law regarding substitute heirs in the two decisions, as well as to reveal the judge's views in determining decisions based on legal facts and applicable provisions. Design/Methodology/Approach: This research uses a normative legal research method with a statutory approach (statute approach) and case study approach (case approach). Data were obtained from a literature study of laws and regulations, the Compilation of Islamic Law (KHI), and official copies of the court decisions studied. Findings: The research results show that both decisions share similarities in recognizing the validity of Article 185 of the Compilation of Islamic Law (KHI), which grants rights to successor heirs. However, there are differences in the distribution of inheritance shares and recognition of lineage relationships, which are influenced by the facts and evidence presented at trial. The judges' views in both decisions reflect a balance between the application of legal norms, the principle of justice, and the specific circumstances of the parties. Paper Type: Research Article